Temperature Ranges and Photoperiod Requirements as Determinants of Quality and Yield in Fruit Trees: A Study in Applied Climatology (Comprehensive Journal of Science, 2026)
This study aims to investigate the correlation between climatic elements (temperature and light) and the physiological processes of fruit trees across their different growth stages. It also highlights the compatibility gap between the precise environmental requirements of these trees and the prevailing climatic conditions, which directly affects crop quality and production efficiency. The study adopts descriptive, analytical, and quantitative approaches to analyze thermal and light data for selected species, including date palm, olive, apple, grapevine, and others.The findings reveal that each growth stage (vegetative, flowering, and ripening) has optimal thermal ranges that cannot be exceeded without causing physiological disturbances. The results indicate that date palms and pomegranates require a high cumulative heat unit ranging from 5000 to 6000 degree-days, whereas these requirements decrease in apples and stone fruits to 2000–3000 degree-days. The study also confirms the importance of thermal amplitude (diurnal temperature variation) in regulating the balance between photosynthesis and respiration, considering the difference between day and night temperatures a critical factor in the accumulation of sugars and pigments.Regarding light, the study demonstrates a specific response to different wavelengths, where photosynthetic efficiency peaks within the ranges of 0.61–0.72 µm and 0.40–0.51 µm.The study recommends aligning the thermal characteristics of geographical regions with the biological requirements of crops prior to cultivation, and using cumulative heat units as an indicator to predict ripening times and crop quality. It also emphasizes the importance of developing a scientific database to support sustainable agricultural planning and to address the challenges of climate change.